2015
DOI: 10.1162/jocn_a_00717
|View full text |Cite
|
Sign up to set email alerts
|

Relating Hippocampus to Relational Memory Processing across Domains and Delays

Abstract: The hippocampus has been implicated in a diverse set of cognitive domains and paradigms, including cognitive mapping, long-term memory, and relational memory, at long or short study–test intervals. Despite the diversity of these areas, their association with the hippocampus may rely on an underlying commonality of relational memory processing shared among them. Most studies assess hippocampal memory within just one of these domains, making it difficult to know whether these paradigms all assess a similar under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 55 publications
6
61
0
1
Order By: Relevance
“…This result was obtained even though delayed-memory task performance correlated significantly with SR task performance in the current sample (SRd: r = 0.59, p = 0.010*; SRa: r = 0.58, p = 0.012*). We note that in our recent study comparing hippocampal volume in older adults to multiple measures of memory performance (Monti et al, 2015), correlations of hippocampal volume were weaker with delayed recall performance than with SR task performance, suggesting that perhaps these standard neuropsychological tests may be less sensitive to differences in hippocampal integrity than the SR task performance measures used here. Moreover, performance on both delayed-memory tasks exhibited less variation (words: 24.2% and stories: 23.2%) than did the SR (SRd and SRa) performance measures here (28.2% and 46.5%), consistent with the idea that the SR task is more sensitive to functional differences within a normal, homogeneous population than are the more standard neuropsychological measures used here.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…This result was obtained even though delayed-memory task performance correlated significantly with SR task performance in the current sample (SRd: r = 0.59, p = 0.010*; SRa: r = 0.58, p = 0.012*). We note that in our recent study comparing hippocampal volume in older adults to multiple measures of memory performance (Monti et al, 2015), correlations of hippocampal volume were weaker with delayed recall performance than with SR task performance, suggesting that perhaps these standard neuropsychological tests may be less sensitive to differences in hippocampal integrity than the SR task performance measures used here. Moreover, performance on both delayed-memory tasks exhibited less variation (words: 24.2% and stories: 23.2%) than did the SR (SRd and SRa) performance measures here (28.2% and 46.5%), consistent with the idea that the SR task is more sensitive to functional differences within a normal, homogeneous population than are the more standard neuropsychological measures used here.…”
Section: Resultsmentioning
confidence: 60%
“…A previous study found that SR performance, and particularly SRa performance, significantly correlated with volume (Monti et al, 2015). However, that work incorporated subjects across a broad age range expected to have substantial variations in volume, whereas in the current population, with a much narrower age range (18–33 yo), we found a very small distribution of bilateral hippocampal volumes (9.27 cm 3 ± 7.7%).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations